Development of mobile road traffic infraction registration system - Rad, Habibollah Arasteh (2010)
The rapid development of roads and the increasing number of vehicles has complicated the road traffic enforcement due to limited resources of the traffic police especially when traffic infraction registration is done manually in many countries. In an effort to improve the efficiency of Iranian traffic police, a computer-based method for mobile road traffic infraction registration is proposed. The study attempts to obtain results that the Iranian traffic police can make decisions base on them to migrate from manual-method towards computer-based method. In order to capture data in this study, questionnaire and interview were used. The system prototype has been developed based on the requirement of Iranian traffic police. The study then concentrates on the Traffic Police Data Center and evaluates the system performance. To facilitate of the decision, the server (i.e. Traffic Police Data Center)and the clients (i.e. police officers) are collectively modeled as an open queuing network. The details of statistical analysis were conducted to obtain the mean server arrival rate (A) of model with respect to real historical data. We concluded the process forms as Non-Homogeneous Poisson Processes. Several analysis techniques were also utilized to assure the accuracy of the estimation. The mean service rate was measured by a specially developed benchmark tool. The tool was configured to imitate several scenarios based on Iranian traffic infraction registration in 2007, and statistics were gathered. The study has used computer simulation as an effective way to solve the queuing problem and evaluating the performance of the system. Therefore, we obtain closed form expressions for the performance metrics with respect to various arrival rates. The simulation results show that the system is reliable even for more than triple amount of the real load. The system resource is also monitored for various performance tests. The server resources are stable at the expected level even under critical loads. Finally, the study has shown that the mobile method has made possible the electronic submission of ticket data, which will result in cost savings for traffic police.